Sağlık Odaklı Liderlik Ölçeğinin Türkçeye Uyarlanması ve Sağlık Odaklı Liderliğin Duygusal Tükenmeye Etkisi: Psikolojik Dayanıklılığın Aracı Rolü - Kerse, Gökhan; Soyalın, Mesut; Özdemir, Şefik (Muş Alparslan Üniversitesi, 2021)
This research aimed to address the concept of “Health-Oriented Leadership (HoL)” and to adapt this leadership scale into Turkish. However, this research also aimed to determine whether the perception of health-oriented leadership directly or indirectly (through psychological resilience) had an effect on emotional exhaustion. Ethical approval was obtained from Aksaray University Human Research Ethics Committee (dated 2021/05-53 and numbered) for the study. For these purposes, data were collected from two different samples. It was tried to reach the goals by making statistical analyzes of the data. The data obtained from the first sample (university administrative staff) were analyzed for the reliability and construct validity of the health-oriented leadership scale. The findings showed that the necessary criteria were met. The data obtained from the second sample (teachers) were used to verify the reliability and validity of the scale and to test the research hypotheses. Analysis findings confirmed the factor structure in the first sample and showed that the scale was reliable. Therefore, it has been determined that the Health-Oriented Leadership Scale can be used in Turkish studies. In addition, analyzes have shown that health-oriented leadership affects emotional exhaustion both directly and via psychological resilience (ie indirectly). In other words, the perception of health-oriented leadership reduces emotional exhaustion both directly and indirectly (by increasing psychological resilience).

Bu araştırma “Sağlık Odaklı Liderlik (SOL)” kavramını ele almayı ve bu liderlik algısı ile ilgili bir ölçeğin uyarlamasını yapmayı amaçlamıştır. Bununla birlikte araştırma sağlık odaklı liderlik algısının doğrudan ve dolaylı olarak (psikolojik dayanıklılık üzerinden) duygusal tükenmeye etkisinin olup olmadığını tespit etmeyi de amaçlamıştır. Bu doğrultuda iki farklı örneklemden veriler toplanmış ve istatistiksel analizler yapılarak amaçlara ulaşılmaya çalışılmıştır. Araştırma için Aksaray Üniversitesi İnsan Araştırmaları Etik Kurulu’ndan (2021/05-53 tarih ve sayılı) gerekli izin alınmıştır. Araştırmada birinci çalışmaya ait örneklemden (üniversite idari personelleri) elde edilen verilerle sağlık odaklı liderlik ölçeğinin güvenilirliği ve yapı geçerliliği için analizler yapılmış ve gerekli kriterler sağlanmıştır. İkinci çalışmaya ait örneklemden elde edilen veriler (öğretmenler) ise ölçek güvenilirliğini ve geçerliliğini doğrulamak ve araştırma hipotezlerini test etmek için kullanılmıştır. Analiz bulguları birinci çalışmadaki faktör yapısını doğrulamış ve güvenilirliğin sağlandığını göstermiştir. Dolayısıyla Sağlık Odaklı Liderlik Ölçeği’nin Türkiye’deki çalışmalarda kullanılabileceği belirlenmiştir. Ayrıca yapılan analizlerde sağlık odaklı liderliğin hem doğrudan hem de psikolojik dayanıklılık aracılığıyla (yani dolaylı olarak) duygusal tükenmeyi etkilediği görülmüştür. Bir diğer ifadeyle, sağlık odaklı liderlik algısı hem doğrudan hem de dolaylı olarak (psikolojik dayanıklılığı artırarak) duygusal tükenmeyi azaltmıştır.
Turkish Adaptation of the Health-Oriented Leadership Scale and Effect of Health-Oriented Leadership on Emotional Exhaustion: the Mediating Role of Psychological Resilience
anemon
Keywords: Health-Oriented Leadership; Psychological Resilience; Emotional Exhaustion; Scale Adaptation; Sağlık Odaklı Liderlik; Psikolojik Dayanıklılık; Duygusal Tükenme; Ölçek Uyarlama